1985
DOI: 10.1111/j.1749-6632.1985.tb20829.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Residual Radiation Effect in the Murine Hematopoietic Stem Cell Compartmenta

Abstract: For the measurement of long-term residual radiation effect in the murine hematopoietic system a test system was developed that quantifies the proliferation ability of progeny of spleen repopulating cells by the proliferation factor (PF). The PF expresses the ratios of 125IUdR incorporation in the recipient spleens at days 3 and 5 following cell transfusion, thus measuring the relative increase in number of proliferating cells. Following 500 rad whole-body gamma irradiation, PF recovered up to 6 months and rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…39 In this study we then focused on long-term follow-up to assess whether the cytokines selected and their combinations could behave as long-term protectors. In fact, if numerous studies conducted in mice have accounted for long-term follow-up, [40][41][42][43] data on the effects in aging irradiated animals of early cytokine administration are lacking. In our study, delayed death mainly observed from day 150 after TBI was likely to occur from hematologic failure (hematopoietic and thrombotic disorders) and nonhematopoietic defects (fibrosis-associated multiorgan failure).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 In this study we then focused on long-term follow-up to assess whether the cytokines selected and their combinations could behave as long-term protectors. In fact, if numerous studies conducted in mice have accounted for long-term follow-up, [40][41][42][43] data on the effects in aging irradiated animals of early cytokine administration are lacking. In our study, delayed death mainly observed from day 150 after TBI was likely to occur from hematologic failure (hematopoietic and thrombotic disorders) and nonhematopoietic defects (fibrosis-associated multiorgan failure).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, irradiated control animals displayed no response, but a transient profound phase of thrombocytopenia (F.H., M.D., manuscript in preparation) (3) reduced effectiveness of residual stem cells. 41,45 One can wonder whether the level of HSPC depletion could be related to the multiple cytokine composition of the combination (4F and 5F) or short-term treatment and whether in this context high survival rates paradoxically are obtained at the expense of the HSPC compartment. We found that 5F-treated animals exhibited increased BM megakaryocytes.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern of regeneration within the pool of early hematopoietic precursor cells is different from the regeneration of both the quality and the number of CFU-S [5,10,22] and may be an expression of proliferative compensation. This proliferative compensation obviously disguises persisting quantitative and qualitative damage in the compartment of CFU-S and thus expresses an enhanced stimulus for proliferation [23].…”
Section: Discussionmentioning
confidence: 99%
“…This proliferative compensation obviously disguises persisting quantitative and qualitative damage in the compartment of CFU-S and thus expresses an enhanced stimulus for proliferation [23]. Selfrenewal of other early precursors, such as CFU-C [22], may as well be involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation